Geschiedenis van het tijdperk van 25-jarigen vrede: 1849-1874 - Andriessen, P. J. (Pieter Jacob), 1815-1877 (Salt Lake City, UT : Project Gutenberg, 2010)
"Geschiedenis van het tijdperk van 25-jarigen vrede: 1849-1874" by P. J. Andriessen is a historical account written in the mid-19th century. The book reflects on a significant period of peace and prosperity in the Netherlands, exploring the events that unfolded during these years. It captures the essence of a nation's relationship with its monarchy, specifically focusing on the reign of King Willem III. The opening of the text sets the scene for the historical narrative by describing the anticipation of a festive event in Amsterdam$1 (Bthe royal celebration of King Willem III$1 (Bs entry into the city. Two young characters, Gustaaf and his sister Margot, are introduced as they eagerly await the arrival of the King by train, engaging in conversations about their society's concerns, such as the moral ramifications of slavery and the nation's debts. This dialogue hints at the broader themes of national identity and progress that the book will explore, emphasizing the significance of royal events in shaping public sentiment and pride. The narrative also presents a rich backdrop of character interactions that will weave through the historical recounting of the period. (This is an automatically generated summary.)s
Release date is 2010-10-01
Produced by The Online Distributed Proofreading Team at http://www.pgdp.net for Project Gutenberg (http://www.gutenberg.org)
Keywords: Netherlands -- History -- 19th century